2017
DOI: 10.1002/ajoc.201700120
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Catalytic Process with a High Eco‐Scale Score for the Synthesis of Five‐, Six‐, and Seven‐Membered Heterocyclic Compounds Using Nanocrystalline Zeolites

Abstract: Nanocrystalline ZSM-5 and Beta zeolites were evaluated as catalysts for the one-pot synthesis of aw ide range of five-, six-, and seven-memberedh eterocyclic compounds. Seven-membered compounds were prepared by the reaction of o-phenylenediamine and ketones, whereas five-membered compounds were obtained when o-aminothiophenol was reactedw ith ketones under the same reactionc ondition. Severalo ther seven-membered compounds werep repared by the reaction of (E)-chalcone with o-phenylenediamine/o-aminothiophenol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Heterocyclic compounds are prepared using hazardous synthesis process. Recently we showed that five-, six-, and seven-member heterocyclic compounds can be prepared by o -aminothiophenol and o -phenylenediamine using nanocrystalline zeolites . In the present study, five-membered benzimidazole and benzothiazole were prepared by highly eco-friendly synthesis process.…”
Section: Resultsmentioning
confidence: 87%
“…Heterocyclic compounds are prepared using hazardous synthesis process. Recently we showed that five-, six-, and seven-member heterocyclic compounds can be prepared by o -aminothiophenol and o -phenylenediamine using nanocrystalline zeolites . In the present study, five-membered benzimidazole and benzothiazole were prepared by highly eco-friendly synthesis process.…”
Section: Resultsmentioning
confidence: 87%
“…E-factor can be represented as the mass ratio of waste generated to the desired product. The eco-score is calculated based on the reported procedure described in our previous study . Eco-score and E-factor are calculated for some of the reactions investigated in this study and provided in Tables S6 and S7.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysis and industrial researchers are making significant efforts to develop catalysts and reagents in order to improve the efficiency of such single-step processes . The 21st century is currently witnessing consistent development of environmentally friendly synthesis processes (with high Eco Score and E-factor) to get the desired products in high yield . An exponential growth in the synthesis and use of heterogeneous catalysts is taking place all over the world .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghosh et al reported a highly efficient, rapid and environment-benign protocol for the synthesis of Hantzsch 1,4dihydropyridine (18) under visible light irradiation via a onepot three-component reaction of aldehydes (15), ethyl acetoacetate ( 16) and ammonium hydroxide (17) in aqueous ethanol with excellent yields (92 %) (Scheme 9). [32] According to the suggested mechanism, a radical anion 10 A was formed by an electron transfer from ammonia (17) to the carbonyl group of ethyl acetoacetate (16) in the presence of light.…”
Section: Synthesis Of Dihydropyridine Derivativesmentioning
confidence: 99%